2023
DOI: 10.7759/cureus.51293
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance, Knowledge, and Attitude of Parents Toward the Human Papillomavirus Vaccine in the Eastern Region of Saudi Arabia: A Cross-Sectional Study

Latteefah Alnaeem,
Shatha Alanizi,
Ghaida AlQarni
et al.

Abstract: Background Human papillomavirus (HPV) is a common sexually transmitted virus associated with conditions such as skin warts and cervical cancer. Although many individuals clear the infection, some face persistent risks. Cervical cancer, which is linked to certain types of HPV, is a major health concern both globally and in Saudi Arabia, with preventive measures including HPV vaccination. However, parental knowledge and attitudes toward vaccinating their children vary. Therefore, this research aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Moreover, a cross-sectional study carried out in the eastern region of Saudi Arabia revealed a connection between sociodemographic variables, such as gender, age, education, employment, and number of children, and the level of awareness and willingness to accept the HPV vaccine. This implies that specifically addressing these factors could greatly enhance both knowledge and vaccination rates [10]. Furthermore, a comparable outcome was obtained in the southwestern region, indicating a lack of understanding among the participants.…”
Section: Figure 2: Proportion Of Good Knowledge Level and Poor Knowle...mentioning
confidence: 81%
“…Moreover, a cross-sectional study carried out in the eastern region of Saudi Arabia revealed a connection between sociodemographic variables, such as gender, age, education, employment, and number of children, and the level of awareness and willingness to accept the HPV vaccine. This implies that specifically addressing these factors could greatly enhance both knowledge and vaccination rates [10]. Furthermore, a comparable outcome was obtained in the southwestern region, indicating a lack of understanding among the participants.…”
Section: Figure 2: Proportion Of Good Knowledge Level and Poor Knowle...mentioning
confidence: 81%
“…Despite the availability of HPV vaccines and the inclusion of HPV vaccination in the national immunization program since 2018, vaccination coverage remains low [9]. Several factors contribute to the low uptake of HPV vaccination in Saudi Arabia, including limited awareness and knowledge about HPV and cervical cancer, cultural and religious beliefs, concerns about vaccine safety and efficacy, and healthcare system-related barriers [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%